Syringic acid: structural elucidation and co-crystallization - Thipparaboina, Rajesh; Mittapalli, Sudhir; Thatikonda, Sowjanya; Nangia, Ashwini; Naidu, V. G. M.; Shastri, Nalini R. (Crystal Growth & Design, 2016)
Syringic acid (SYRA) is a potential antioxidant used in traditional Chinese medicine and is an emerging nutraceutical. Current reports claim its potential anti-angiogenic, anti-glycating, anti-hyperglycaemic, neuroprotective, and memory-enhancing properties in various animal models. To date, SYRA crystal structure has not been elucidated, and no crystal engineering studies have been reported. This study reports the crystal structure of SYRA for the first time along with its nicotinamide (SNCT-E) and urea (SU-EA-M) co-crystals. All forms were successfully characterized using single crystal X-ray diffraction (XRD), powder XRD, and differential scanning calorimetry. Single crystal analysis revealed that SYRA crystallized in the C2/c space group, whereas SNCT-E (2:1) and SU-EA-M (1:2) crystallized in the P21/n and Cmca space group, respectively. Novel co-crystals have shown improved solubility, modified dissolution profiles, and improved flow and compressibility. Cytotoxic effects were explored in DU145 prostate cancer cell lines for the first time, and significant enhancement in cytotoxicity by the co-crystals was observed compared to plain components. A two-fold increase in % cytotoxicity of SNCT-E was observed when compared to the corresponding physical mixture. These studies shed light on potential utility of SYRA as a coformer for various pharmaceutical applications to design synergistic and organ-protective co-crystals.

Rufinamide: crystal structure elucidation and solid state characterization - Salunke, Nita; Thipparaboina, Rajesh; Chavan, Rahul B.; Lodagekar, Anurag; Mittapalli, Sudhir; Nangia, Ashwini; Shastri, Nalini R. (Journal of Pharmaceutical and Biomedical Analysis, 2018)
Rufinamide (R) is a triazole derivative approved for the management of partial seizures and seizures associated with Lennox-Gastaut Syndrome, in November 2007. Crystal structure, solid state characterization, drug-excipient compatibility and solubility play a pivotal role in formulation development. This work deals with the crystal structure elucidation of R by single crystal X-ray diffraction and solid state characterization by thermal, spectroscopic and crystallographic techniques. Drug- excipient compatibility was assessed by differential scanning calorimetry (DSC). New RP-HPLC method for quantification of R was developed with improved retention time. Solubility and dissolution of drug in different media was determined. Additionally, the flow behavior of the drug was evaluated by measuring Carr's index and Hausner's ratio, while the compressibility behavior was studied using Well's protocol. R crystallized from dimethylformamide (R-DMF) was utilized for single crystal analysis. The drug crystallized in triclinic crystal system with P-1 space group. Asymmetric unit cell consists of two molecules of R held by intermolecular hydrogen bond (connected by N-H center dot center dot center dot O, which forms the catemeric chain). Analytical outcomes from DSC, thermogravimetric analysis (TGA) and powder X-ray diffraction (PXRD) revealed that the drug was present in pure crystalline form and was devoid of any polymorphic or pseudopolymorphic impurities. Influence of pH on the solubility and dissolution of R-DMF was found to be insignificant. The drug exhibited poor aqueous solubility, which was improved nearly 4.6 fold with the addition of 2% sodium lauryl sulphate (SLS). The drug exhibits poor flow and elastic compression nature. Excipients such as poly ethylene glycol (PEG) 8000, SLS, lactose monohydrate, starch and Hydroxypropyl methylcellulose (HPMC) E15 were incompatible with R-DMF as identified by thermal analysis. It is envisaged that these information regarding solid state properties of R-DMF would aid in identifying a logical path for formulation development. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Compressibility; Dissolution media; DSC; HPLC method; solubility

Hepatoprotective cocrystals of isoniazid: synthesis, solid state characterization, and hepatotoxicity studies - Yadav, Balvant; Gunnam, Anilkumar; Thipparaboina, Rajesh; Nangia, Ashwini K.; Shastri, Nalini R. (Crystal Growth & Design, 2019)
Isoniazid (INH) is one of the first line drugs used in combination with pyrazinamide and rifampicin for the management of tuberculosis. Idiosyncratic hepatotoxicity is one of the most common side effects of antitubercular therapy worldwide. The current study explores solid phase modification of INH by cocrystallization with various hepatoprotective coformers, namely chrysin, hesperetin, silibinin, syringic acid (SYRA), and quercetin (QUE) to address hepatotoxicity concerns. Cocrystals were obtained with SYRA and QUE. Supramolecular synthons based on pyridine-carboxyl and pyridine-hydroxyl synthon enabled the formation of cocrystals. INHSYRA and INHQUE cocrystals were characterized by FT-IR, DSC, and PXRD. Single crystal X-ray analysis of INHSYRA revealed that it crystallized in triclinic system with the P (1) over bar space group. Intrinsic dissolution rate studies (IDR) showed slow drug release from both the cocrystals. Hepatoprotective effects of INHSYRA and INHQUE cocrystals were evaluated by a single toxic dose study and a subchronic study for 28 days. Results from the subchronic study indicated significant increase in ALT, AST, and ALP enzyme levels in the INH-treated group whereas the enzyme levels in INHSYRA and INHQUE cocrystal treated group were comparable to that of the untreated group. This study demonstrates the in vivo hepatoprotective effects of coformers SYRA and QUE provide promising evidence for utility of nutraceutical based coformers, to tackle hepatotoxicity associated with various drugs.